NUMERICAL INVESTIGATIONS ON HEAT TRANSFER AND FLOW STRUCTURE IN A CIRCULAR TUBE WITH VARIOUS SHAPES OF WINGLET VORTEX GENERATORS - Withada Jedsadaratanachai; Amnart Boonloi (My University, 2016)
A premiere free-access and peer-reviewed frontier journal site, serving the needs of the thermal-fluids community. See the latest research or submit an article. Quickly share your research with the global thermal-fluids community, for increased citations and impact at no cost.
Keywords: Wingtip device; Thermal fluids; Vortex generator; Frontier; Heat Transfer and Boiling Studies